Optimalisasi Terminal Tipe A Bandar Raya Payung Sekaki Kota Pekanbaru Provinsi Riau - Anggi Pratama; Tonny Judiantono (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Terminal Type A Bandar Raya Payung Sekaki is the largest terminal in the city of Pekanbaru and Riau Province with quite volatile arrival and departure movements. The current condition of the BRPS Terminal is not as expected because there are still many passengers who are reluctant to get on and off at the terminal because the location of the terminal is quite far from the center of activities such as the center of trade, socio-economic and other activities so that there is a lack of movement through the BRPS Terminal. The analytical method used is qualitative and quantitative analysis. Qualitative analysis is used to describe current conditions such as system activity conditions, terminal utilization, terminal accessibility and SWOT. While the quantitative analysis is IPA analysis, movement and passenger potential analysis using growth factors and terminal income potential analysis. From the results of the SWOT analysis, it is stated that the terminal is in quadrant I (aggressive). From the results of the IPA, there are 15 service indicators that need to be improved. From the analysis of potential demand, there are 25.34% additional passengers for AKDP and 41.61% for AKAP. From the results of the analysis of potential income has a potential income of Rp. 569,250,000/year of potential land lease. Based on the analysis of potential demand and income, the terminal has great potential to be optimized. Terminal optimization is carried out by improving terminal services, increasing terminal accessibility and connectivity Abstrak. Terminal Tipe A Bandar Raya Payung Sekaki merupakan terminal terbesar di kota Pekanbaru dan Provinsi Riau dengan pergerakan kedatangan dan keberangkatan yang cukup fluktuatif. Kondisi Terminal BRPS saat ini tidak seperti yang diharapkan karena masih banyak penumpang yang enggan naik dan turun di terminal karena lokasi terminal berada cukup jauh dari pusat kegiatan seperti pusat perdagangan, sosial ekonomi dan kegiatan lainnya sehingga kurangnya pergerakan yang melewati Terminal BRPS. Metode analisis yang digunakan adalah analisis kualitatif dan kuantitatif. Analisis kualitatif digunakan untuk menggambarkan kondisi terkini seperti kondisi sistem aktivitas, pemanfaatan terminal, aksesibilitas terminal dan SWOT. Sedangkan analisis kuantitatif yaitu analisis IPA, analisis potensi pergerakan dan penumpang menggunakan growth factor dan analisis potensi pendapatan terminal. Dari hasil analisis SWOT menyatakan terminal berada di kuadran I (agresif). Dari hasil IPA terdapat 15 indikator pelayanan yang perlu ditingkatkan. Dari hasil analisis potensi demand terdapat penambahan penumpang AKDP 25,34% dan AKAP 41,61%. Dari hasil analisis potensi pendapatan memiliki pendapatan potensial sebesar Rp. 569.250.000/tahun dari sewa lahan potensial. Berdasarkan hasil analisis potensi demand dan pendapatan maka terminal memiliki potensi yang besar untuk dioptimalkan. Optimalisasi terminal dilakukan dengan cara meningkatan pelayanan terminal, meningkatan aksesibilitas dan konektivitas terminal